The impact of a comprehensive electronic patient portal on the health service use: an interrupted time-series analysis. (12th December 2018) - Martínez Nicolás, Ismael; Lê Cook, Benjamin; Flores, Michael; Del Olmo Rodriguez, Marta; Hernández Rodríguez, Corazón; Llamas Sillero, Pilar; Baca-Garcia, Enrique
Abstract: Background: There is little empirical research on the potential benefit that electronic patient portals (EPP) can have on the care quality and health outcomes of diverse multi-ethnic international populations. The purpose of this study is to determine the extent to which an EPP was associated with improvements in health service use. Methods: Using a quasi-experimental interrupted time-series approach, we assessed health service use before (April 2012–September 2015) and after (October 2015–December 2016) the implementation of a comprehensive EPP at four hospitals in Madrid, Spain. Primary outcomes were number of outpatient visits, any hospital admission, any 30-day all-cause readmission and any emergency department visit. Results: Implementation of the EPP was associated with a significant decline in readmissions. Among patients with chronic heart failure, EPP implementation was associated with a significant decline for all outcome measures, and among patients with COPD, a decline in all outcomes except readmissions. Among patients diagnosed with malignant hematological diseases, no significant changes were identified. Conclusions: EPPs hold promise for reducing hospital readmissions. Certain patient populations with chronic conditions may differentially benefit from portal use depending on their needs for communication with their providers.